Climbing the Protest Pyramid: A Situational Analysis of the Resistance of Rickshaw Drivers in Guangzhou, China - Xu, Jianhua (International journal of offender therapy and comparative criminology, 2021)
Guangzhou police confiscated more than 1,000 “illegal” rickshaws every day since they were banned from use in the city. However, rickshaws were omnipresent in all corners of the city, representing a massive army of unemployed or underemployed workers struggling to eke out a living. Various strategies were used by these rickshaw operators to protest and resist the mass confiscation by the police. Using data collected through systematic social observation of police law enforcement and rickshaw drivers’ routine activities, focus group interviews with the police, in-depth semistructured interviews with rickshaw drivers, official police detention statistics of rickshaw drivers, and media content data mining, this article provides a typology and an analysis of resistance. Based on the severity and intensity of resistance, these typologies are ranked in what I shall call a “pyramid of resistance.” This article further examines how situational factors such as degree of frustration, procedural justice, mobilization capacity, and campaign-style policing affect the escalation of resistance.